Islam in the Malay world; an overview - Zakariya, Hafiz (2019)
This lecture discusses the meanings of the Malay world. After providing a concise discussion on the above issue, it analyzes the processes of the introduction and the spread of Islam in the region. It also analyzes the factors responsible for the shaping of Islam in the Malay world as the "moderate' and "friendly" Islam To understand this . we need to back in history exploring the various factors responsible for the formulation of such attitude in the Malay world.